Student Development Talk Series: New Year, New Me ~ Mentally and Emotionally Ready to New Challenges - Amalia, Madihie (Universiti Malaysia Sarawak (UNIMAS), 2021)
A special welcoming Year 2021 to all university students through Student Development Series by Pusat Pemajuan Pelajar, Universiti Malaysia Sarawak. Amalia Madihie is a counsellor educator in Malaysia will deliver her first webinar in 2021 on a special topic: New Year, New Me ~ Mentally and Emotionally Ready to New Challenges. Amalia will focus on mental health among university students.